2010
DOI: 10.1007/s10018-009-0159-4
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the environmental Kuznets curve: scale, technique, and composition effects

Abstract: Economic growth, Environmental Kuznets curve, Scale effect, Technique effect, Composition effect,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 38 publications
7
100
1
1
Order By: Relevance
“…The results show that 1% increase in composition effect (capital-labor ratio) leads to decrease CO 2 emissions by 0.57% keeping all else same. This finding is consistent with Tsurumi and Managi (2010), but contrasting to Cole (2006) who reported that composition effect is positively linked with energy intensity and leads CO 2 emissions. This notion further enumerates that change in the composition of production line (i.e.…”
Section: Ectsupporting
confidence: 87%
“…The results show that 1% increase in composition effect (capital-labor ratio) leads to decrease CO 2 emissions by 0.57% keeping all else same. This finding is consistent with Tsurumi and Managi (2010), but contrasting to Cole (2006) who reported that composition effect is positively linked with energy intensity and leads CO 2 emissions. This notion further enumerates that change in the composition of production line (i.e.…”
Section: Ectsupporting
confidence: 87%
“…Crosscountry EKC analysis tends to show the close relationship between environmental emissions and gross domestic product (GDP) or related policy variables (Farzin and Bond, 2006;Wagner, 2008;Galeotti et al, 2009;Tsurumi and Managi, 2010). 1 The EKC hypothesis has been tested in many countries using various pollutant data.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are (1) economic scale, (2) technology level, and (3) industrial composition effects. The industrial composition effect is especially difficult to interpret with respect to the EKC (Tsurumi and Managi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is also necessary to examine the relationship between income or economic growth and environmental quality (Stern et al, 1996;Harbaugh et al, 2002;Rezek and Rogers, 2008); and decompose the determinants of environmental performance or consider whether environmental policy could be more stringent when the technique effect could not sufficiently reduce emissions (Panayotou, 1997;Tsurumi and Managi, 2010).…”
Section: Reason Discussionmentioning
confidence: 99%